As manifestações afetivas nas aulas de educação física: análise de uma classe de 3ª série do ensino fundamental na perspectiva de Henri Wallon - Monteiro, Mario Destro (2006)
This study aimed to understand how the affective dimension manifests in physical education classes on the third grade of elementary school at a public school in the north region of the city of São Paulo. Five classes were observed, at only one third grade class, with the same physical education teacher. The data harvesting and analysis were guided by Henri Wallon s psychogenetic theory. The observations were described, guided by the research s problem, with the influence of affectivity concepts that this theorical conception presents and put in attached. Later, we grouped in sensations of satisfaction and indisposition, both from the teachers and the students, and raised manifestation categories that were captured by the researcher. The results obtained revealed the little importance given by teacher towards the student s manifestations. The indisposition manifestations were more abundant than the satisfaction manifestations. This calls our attention, mainly to physical education teachers, so that they can rethink their practices, having as a basis the improvement of the pedagogical context, which respects sensibly the needs of the students and teachers